Mechanical response and actuation fatigue behavior of Nb-nanowire enhanced NiTiHf high temperature shape memory alloy wires. (September 2022) - Huo, Xinyu; Jin, Mingjiang; Jin, Qi; Lahkar, Simanta; Huang, Guangfa; Lu, Weijie; Wang, Xiaodong
Abstract: This study elucidates the influence of Nb addition on the mechanical and actuation response of the (Ni49.5 Ti35.5 Hf15 )90 Nb10 high temperature shape memory alloy (HTSMA) wires and presents the microstructure evolution of Nb with the drawing process. The change in morphology of β-Nb from network structure to nanowires greatly increases the yield strength of the NiTiHfNb alloy followed by an ascending stress plateau. The fatigue life of the (Ni49.5 Ti35.5 Hf15 )90 Nb10 wire is 7754 cycles with remarkably stable actuation strain of 2.3% under 418 MPa. The concept of in-situ nanowire composite is applied to HTSMAs for the first time and our finding implies the promising practical applications of NiTiHfNb wires in high temperature actuators. Graphical abstract: Image, graphical abstract